RESOURCE-CONSTRAINED ASSEMBLY LINE BALANCING PROBLEM AND AN APPLICATION IN AN ASSEMBLY LINE - Mehmet Ceylan; Seda Hezer (Eskişehir Osmangazi Üniversitesi Mühendislik ve Mimarlık Fakültesi Dergisi)
One of the most important ways to increase productivity in industrial manufacturing is the efficient design of assembly lines. These lines consist of workstations connected by moving belts or conveyors where products are assembled part by part to reach their final form. In today's competitive manufacturing environment, organizing the work to be performed at these stations in the most efficient way is critically important. This organization process is called the “Assembly Line Balancing Problem (ALBP)” and primarily focuses on two main objectives: minimizing the number of workstations and cycle time. However, recently, this classical approach has given way to a more comprehensive perspective. Now, the optimization of resources such as workers, machines, equipment, and energy is also included in the problem. This advanced problem is termed the “Resource-Constrained ALBP (RCALBP)”. Within the scope of this study, the “Multi-Model RCALBP (MRCALBP)” was implemented in a company manufacturing industrial kitchen machines. Based on a known mathematical model in the RCALBP literature, a solution has been developed adapted to the specific needs of the company. Successful results were achieved through optimization work using 19 different resources for four different products. Two separate production lines were merged into one line, total number of resources was reduced from 46 to 31, and the number of workers was decreased from 4 to 2. At least 49% improvement in total costs has been achieved for each product. This study demonstrates that theoretical models can be successfully applied in real life and provide tangible benefits.